The Racial Politics of Emotion: Teaching an Interdisciplinary Border Institute in the Midwest. Issue 2 (May 2021) - Colón, Sigma; Jiménez-Anglada, Thelma; Smith, Jesús Gregorio
The militarization of the U.S.-Mexico border, criminalization of immigrants and migrants, and humanitarian emergency surrounding the border has negatively impacted students and schools. Responding to the impact of U.S. border politics on education, we taught a week-long institute for local teachers to learn about the histories and lived experiences connecting the Central American, Mexican, and U.S. borders. During the institute we asked participants—who were predominantly white K-12 teachers—to reflect on their learning experiences in personal journals. The aim of this study was to investigate the racial politics of emotion when confronting border issues in a classroom setting. Taking an interdisciplinary approach to our analysis, we conducted qualitative content analysis and close readings of twenty-one teacher's journals to determine patterns in the emotional response's teachers had to the histories, testimonies, audio, and visual accounts to which they were exposed through readings and seminars. The results of our analysis reveal that emotions were used by participants to maintain racial boundaries and reinforce race-based notions of national belonging, but also to challenge injustice both in and beyond classroom settings. The findings have significant implications about the impact that ethnic studies programs and critical race theory curriculum may have on teacher education.